Design and real-time implementation of data-driven adaptive wide-area damping controller for back-to-back VSC-HVDC. (July 2019) - Zeng, Lingkang; Yao, Wei; Zeng, Qi; Li, Dahu; Fang, Jiakun; Ai, Xiaomeng; Wen, Jinyu; He, Haibo
Graphical abstract: Highlights: A data-driven wide-area damping controller (D-WADC) of BTB-VSC-HVDC is proposed. The D-WADC makes use of the active and reactive power control of BTB-VSC-HVDC. The D-WADC can adapt to the change of system operating condition. The D-WADC can adaptively compensate the stochastic time delay. Both simulation and hardware-in-loop experiment results verify the control effectiveness. Abstract: This paper proposes a data-driven adaptive wide-area damping controller (D-WADC) for back-to-back VSC-HVDC to suppress the low frequency oscillation in a large-scale interconnected power system. The proposed D-WADC adopts a dual-loop control structure to make full use of the active and reactive power control of VSC-HVDC to improve the damping of the power system. A data-driven algorithm named the goal representation heuristic dynamic programming is employed to design the proposed D-WADC, which means the design procedure only requires the input and output data rather than the mathematic model of the concerned power system. Thus, the D-WADC can adapt to the change of operating condition through online weight modification. Besides, the adaptive delay compensator (ADC) is added to effectively compensate the stochastic delay involved in the wide-area feedback signal. Case studies are conducted based on the simplified model of a practical power system and the 16-machine system with a back-to-back VSC-HVDC. Both the simulation and hardware-in-loop experiment results verify that the proposed D-WADC can effectively suppress the low-frequency oscillation under a wide range of operating conditions, disturbances, and stochastic communication delays.